Caracterização físico-química de frutos de híbridos de morangueiro - Souza, Douglas Correa de (2015)
The strawberry breeding programs are seeking for quality attribute improvement, increase yield as well as reduce the production costs. The characterization of the newly released materials is very important in order to understand and explore the external aspects and chemical parameters of the fruit. Therefore, the aim of this study was to characterize the physical-chemical aspects of hybrids of strawberry that achieved notable results from the breeding program of the Universidade Federal de Lavras (UFLA), according to the evaluate characteristic: soluble solids (SS), titratable acidity (TA), firmness, total sugars, soluble pectin, total pectin, pH, ratio SS /TA, size, shape and external and internal colour of the fruit. The experiment design was a completely randomized with 103 hybrid and 7 commercial cultivar. The statistical analysis indicate that MOGSC12-501, MCA12-86, MDA12-37, MFA12-448 and MOGA12-46 hybrids achieved notable results and should be assessed or used as parental in the next stage of the program.